The Effect of Giving PALOSDEL (Oatmeal Avocado Pie and Soy Milk) on Reducing Total Cholesterol Levels in Coronary Heart Disease Patients - Geminsah Putra H Siregar; Erlina Nasution; Fitriyani Pulungan (GLOBAL HEALTH SCIENCE GROUP, 2025)
In Indonesia, annual fatalities from cardiovascular disease total 651,481, including 331,349 deaths from stroke, 245,343 from coronary heart disease, 50,620 from hypertensive heart disease, and additional cases from other cardiovascular conditions. Objective: The purpose of the study was to analyze the effect of giving PALOSDEL (Avocado Oatmeal Pie and Soy Milk) on Reducing Total Cholesterol Levels in Coronary Heart Disease Patients at the Dagang Kelambir Health Center, Tanjung Morawa District, Deli Serdang Regency. Method: This research is a quasi-experimental study using a pre-test and post-test strategy. Where before and after treatment, cholesterol levels were measured. The sample in this study was 30 people. The analysis was conducted using the t-test with a 95% confidence level using the SPSS version 25 application. Results: The results of the study showed that there was an effect of giving PALOSDEL (Avocado Oatmeal Pie and Soy Milk) on the Decrease in Total Cholesterol Levels in Coronary Heart Disease Patients at the Dagang Kelambir Health Center, Tanjung Morawa District, Deli Serdang Regency with the results of the statistical test value p = 0.000. Conclusions: It can be concluded that PALASDOL has an effect on reducing cholesterol levels in coronary heart disease patients.